The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.eats.2020.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Superolateral Portal and 70° Arthroscope to Optimize Visualization of Patellofemoral Tracking and Osteochondral Lesions in Patients With Recurrent Patellar Instability

Abstract: Surgical treatment of patellofemoral instability and associated cartilaginous lesions can be technically challenging. Visualization of patellar tracking and underlying osteochondral lesions is paramount to operative success. To treat these conditions effectively, a comprehensive arthroscopic assessment of the patellofemoral joint as well as dynamic visualization of patella tracking must be achieved. Visualization of the patellofemoral joint—in particular, the articular cartilage of the patella and trochlea mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In this context, Niemeyer et al suggested that any osteochondral flake fracture indicates surgical treatment with the objective for internal fixation in both pediatric and adult patients [24]. Hence, due to the improved understanding of patellofemoral pathologies, a variety of arthroscopic and open surgical concepts for the repair of osteochondral lesions and the restoration of joint stability have been developed [25][26][27][28][29]. Furthermore, additional techniques for deformity correction (e.g., HTO) are inconsistently applied within the body of literature [30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, Niemeyer et al suggested that any osteochondral flake fracture indicates surgical treatment with the objective for internal fixation in both pediatric and adult patients [24]. Hence, due to the improved understanding of patellofemoral pathologies, a variety of arthroscopic and open surgical concepts for the repair of osteochondral lesions and the restoration of joint stability have been developed [25][26][27][28][29]. Furthermore, additional techniques for deformity correction (e.g., HTO) are inconsistently applied within the body of literature [30].…”
Section: Discussionmentioning
confidence: 99%
“…The reviewed literature predominantly comprises low level and quality evidence and is based on variable treatment protocols (Table 1). Furthermore, various methods of internal fixation are employed, including metallic (headless) and resorbable compression screws [23,24,26], Kirschner wires [26], resorbable polylactid implants (nails, pins and darts) [15,[19][20][21][22]25,27,28,31,33], sutures (e.g., PDS) and suture-anchor constructs [29,34,35,47,48], fibrin sealants [19], and bone pegs [32]. Different main outcome measures and follow-up time periods are reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 30 In all cases, diagnostic arthroscopy was carried out to examine for cartilage lesions and qualify trochlear morphology and patellar tracking from a superolateral portal with a 70° arthroscope. 2 In some cases, this guided the treatment decision to include or exclude the TTO. The arthroscope was withdrawn once the patient was deemed an adequate candidate for osteotomy.…”
Section: Methodsmentioning
confidence: 99%
“…In some cases, a 70° arthroscope may be used to improve visualization of the patellar articular surface. 24 It is important to note the extent and location of patellar cartilage wear. In cases of trochlear entrance dysplasia, patellar lesions are most commonly seen along the distal patella.…”
Section: Surgical Technique (With Video Illustration)mentioning
confidence: 99%